Synthesis and characterization of azo amidazole ligand type N2 and metal complexes with di valence cobalt , nickel and copper - Shatha Abdualameer Jawad (Al-Qadisiyah Journal of Pure Science, 2018)
The bi dentate ligand type N2 have been prepared  through two steps . The first included the reaction between one equivalent of benzil with one equnivalent of hexa methylene tetra amine, the second included the reaction of first step precursor with one equnivalent of diazanium chloride ( p- ethyle aniline with acidic sodium nitrate )   ,  to obtained the target ligand . Co+2 , Ni+2 , Cu+2  from there action of the ligand Complexes were prepared with metal ions 1:1 ratio , the prepousd compounds were characterized by  FT-IR , UV-Vis , NMR for ligand , C.H.N Elemental analysis  spectoscopies , as well as the molar conductivity and magneticthe successptibility . suggested  geometry around the cobalte and copper  ions  is  octahedral and Square planer around nickel ion.